Pengaruh Dimensi Budaya Terhadap Perilaku Penggunaan E-commerce: Daerah Istimewa Yogyakarta - Sari, Danar Retno; Dirgahayu, Teduh (Universitas Nusantara PGRI Kediri, 2018)
The use of e-commerce influenced by culture, which consist of five dimensions, such as power distance, individualism, masculinity, uncertainty avoidance, and long-term orientation (Hofsterde, 1984). This paper aim to investigate and explored the effect of culture dimenssion on behavior to use e-commerce in Daerah Istimewa Yogyakarta. Theory Planned Behavior as a model to investigate behavior to use e-commerce. Culture dimensiona as indicator used to support variable in TPB. Our result showed that power distance and masculinity had significant effect on behavior to use e-comerce in Daerah Istimewa Yogyakarta. This factors can be used to create a new marketing strategy for business people. In an academic area, this model can be used as alternative model to predict intentions and individual behavior using information technology, especially e-commerce.